Sustainable Development of Project Management in Energy Companies: The Digital Economy Context - Grzegorz KINELSKI (Communications of International Proceedings, 2020)
Sustainable development is a concept that has recently appeared in economics. The question is what influences the sustainability of development? Can the systematization of project management have a positive impact on the sustainability of the development of a company, sector or economy? How is industry and digital economy influencing sustainable development? We now call Industry 4.0 the fourth industrial revolution. Like the previous ones, it also has the ability to transform economies, jobs and societies. Our expectations are changing to the speed of obtaining answers to the questions asked. This is done by introducing new technologies and processes. Nowadays, it is said that the Industry 4.0 the fourth industrial revolution. Like the previous ones, it as well has the ability to transform economies, jobs and societies. Our expectations are changing to the speed of obtaining answers to the questions asked. This is done by introducing new technologies and processes. This is an opportunity for Polish participants of local heat markets, or participants of the power or energy market. who are currently facing profound changes and investments forced, among others, by BAT conclusions. Such mega-processes as digitization, automation, artificial intelligence, IoT, machine learning is increasingly penetrating the world and business. More than 200 years have passed since the first industrial revolution, which was the use of the steam engine, and the requirements for testing the efficiency of enterprises have changed, which themselves are changing very quickly. The basic efficiency measures used in a given sector often result from the specifics of the sector and its degree of development on a macroeconomic scale. Therefore, it is worth placing the energy company in this environment and presenting its role to better match the instruments used. The above is also associated with increased reporting and the need to use additional evaluation measures, e.g. effectiveness of individual projects. It is therefore worth analyzing the available literature in this area, and the performance measures available and used in it, which will help in assessing the effectiveness of management, despite political and regulatory turmoil, and help us use the opportunities brought by the fourth industrial revolution.
Keywords: Energy management; Sustainable development; project management; economic efficiency; digital economy; energy efficiency.